(untitled) (Global Journal of Medical Research, 2014)
Background: Malarial infection associated with common hematological abnormalities like anemia, Thrombocytopenia, Hemolytic anemia. Hemolytic anemia is due to occurrence of cold agglutinins. This study throws light on the prevalence of cold agglutinins in patients with malarial infection and their detection. Method: About 150 patients diagnosed as having Malaria by Peripheral smear, QBC for malaria or by Rappid diagnostic test for Malaria were studied for occurrence of cold agglutinins by Cold agglutinin test. Results: Out of 150 Patients, who are diagnosed as positive for malaria, 83.3% of the patients had negative for cold agglutinin and only (4%) were found to have high titers of cold agglutinins. The mean age group of the patients who were positive for the test was 45.25 ± 19.7 years. The Hemoglobin percentage and platelet count in cold agglutinin positive patients were 8.85 (± 3.72) gms% and 1, 03, 500 (± 1.16) respectively.